A study on the cause of job stress among employees in Human Resource Department of Bank Rakyat / Nathira Hidzir Pauzi - Hidzir Pauzi, Nathira (Faculty of Business and Management, 2013)
The study is about the cause of job stress among employees in Human Resource Department of Bank Rakyat. The objectives of this study are to investigate the relationship between work overload, career progression, and long working hours as the cause of job stress. The research was carried out at the Human Resource Department of Bank Rakyat at Jalan Tangsi. Both descriptive and inferential statistics were used to analyze the data using the SPSS version 17.0. Correlation analyses were conducted to test the relationship between job stress with work overload, career progression, and long working hours; whereas descriptive analysis was conducted to analyze demographic characteristics of respondents. The findings showed that all three factors have significant and positive relationship with job stress. Findings of this study also resulted in the strong relationship between work overload and job stress, career progression and job stress, and moderate relationship between long working hours and job stress. However, the finding shows that work overload have the strongest relationship with job stress.